ON THE HISTORY OF THE INTERNATIONAL PROJECT OF DEEP ICE-CORE DRILLING AT VOSTOK STATION - V. Kotlyakov M.; В. Котляков М. (Ice and Snow, 2015)
This article describes a history of revealing the Antarctic sub-glacialLakeVostokas well as organization and further progress of the Soviet/Russian deep drilling project in the Central Antarctica, and, thus, the long-standing cooperation between USSR/Russia,Franceand theUSAunder this project. The works lasted for several decades and were successfully completed with penetration into the lake that should be recognized as major achievement in the field of the Earth sciences in the early XXI century. Рассказывается о становлении и развитии советского/российского проекта глубокого бурения в Центральной Антарктиде, об истории открытия подлёдного озера Восток и о многолетнем сотрудничестве СССР/России, Франции и США по этому проекту. Эти работы, продолжавшиеся несколько десятилетий, успешно завершились проникновением в подлёдное озеро, что следует признать крупнейшим достижением начала XXI в. в области наук о Земле.